Knowledge Survey Badminton Extracurricular Students SMA 1 Klari on Injury Handling With The Rice Method - Syirojudin, Haikal Maulana; Firdaus, Rayya Pramandha; Dharmawan, Muhammad Rifki; Setiawan, Muhammad Arief (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to analyze the level of knowledge of badminton extracurricular students at SMA 1 Klari on the RICE (Rest, Ice, Compression, Elevation) method in handling sports injuries. The research method uses a quantitative approach with a descriptive analysis design. Data collection through surveys uses questionnaires created in Google Forms to make it easier for respondents to distribute and fill out. The population in this study is 30 students who are members of the badminton extracurricular at SMA 1 Klari. The sampling technique used purposive sampling, with a sample of 20 students who met the criteria. The questionnaire consists of 20 questions, which include 15 positive statements and 5 negative statements. The scoring scale used is the Guttman scale, with a